2017
DOI: 10.4172/2329-9517.1000277
|View full text |Cite
|
Sign up to set email alerts
|

QRS Complex Duration is a Marker of Reperfusion in Patients Presenting with Acute ST Segment Elevation Myocardial Infarction

Abstract: Background: Acute myocardial ischemia decreases electrical conduction velocity through the ischemic myocardium, the aim of the study is to evaluate the value of the change in QRS complex duration as a marker of reperfusion in patients presenting with ST segment elevation myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Similarly, Magdy et al. has shown in the study of 100 patients that QRS narrowing was significant in patients with a good MBG both at the end of 60th and 90th minutes post angioplasty 11 . All these studies further confirm ischemia as a cause of QRS prolongation and thus, explain the dynamic nature of QRS changes in these patients.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Similarly, Magdy et al. has shown in the study of 100 patients that QRS narrowing was significant in patients with a good MBG both at the end of 60th and 90th minutes post angioplasty 11 . All these studies further confirm ischemia as a cause of QRS prolongation and thus, explain the dynamic nature of QRS changes in these patients.…”
Section: Discussionsupporting
confidence: 52%
“…and Magdy et al. have shown that QRS narrowing of 10 msec was the best discriminative value for reperfusion assessment, which had a sensitivity of 90% and a specificity of around 80% 10, 11. Difference in this cutoff value may be because we had used a computerized method of calculating the QRS duration using EEPEE software, which is more precise and specific than the manual method.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation